1T-phase MoS2/holey ultrathin g-C3N4 nanosheets based 2D/2D heterostructure for enhanced photocatalytic hydrogen production. (5th March 2023) - Xiong, Ya; Liu, Teng; Liu, Wendi; Wang, Xinyu; Xue, Yanjun; Tian, Jian
Abstract: Although graphitic carbon nitride (g-C3 N4 ) is widely used for photocatalytic hydrogen production, its practical application is restricted by the high recombination rate of photoinduced electron-hole pairs and limited active sites. In this work, holey ultrathin g-C3 N4 nanosheets (HCN NSs) with rich active sites are prepared, followed by the growth of 1T-MoS2 NSs on their surfaces to construct 2D/2D 1T-MoS2 /HCN heterostructure. Due to the high surface area and abundant hydrogen active sites of the hybrid, large and intimate 2D nanointerface between MoS2 and HCN, hydrogen ion adsorption and charge separation/transport ability are greatly enhanced. As a result, 1T-MoS2 /HCN-4 with the optimal 1T-MoS2 content of 8 wt% displays the highest H2 production rate of 2724.2 μmol −1  h −1  g −1 under simulated solar light illumination with apparent quantum efficiency of 8.1% (λ = 370 nm). Moreover, the 1T-MoS2 /HCN-4 hybrid manifests improved stability after a long-time test. This study opens the door to design highly-efficient g-C3 N4 based 2D/2D heterostructures for photocatalytic H2 production. Highlights: 2D/2D 1T-MoS2 /HCN has been designed by in-situ growth of 1T-MoS2 nanosheets on the surfaces of holey ultrathin g-C3 N4 (HCN). 8 wt% 1T-MoS2 /HCN displays a high H2 production rate of 2724.2 μmol −1  h −1  g −1 under simulated solar light illumination. The underlying mechanism of improved photocatalytic performance based on 1T-MoS2 /HCN is discussed.